Landslide Mitigation Through Socio-Cultural Approach With Policy of Utilization of Local Wisdom in Pangkalan Sub-District of Lima Puluh Kota - Erianjoni, Erianjoni (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This article is the result of research that attempts to reveal the mitigation of landslide disaster with socio-cultural approach. Seeking to see side of local wisdom of society in District of Lima Puluh Kota of West Sumatera Province conducted by mixed methode by combining data collecting technique that exist in research with approach of qualitative and qualitative, that is questionnaire, observation, interview and Focus Group Discussion (FGD), sampling with purposive sampling technique. data wetting by means of triangulation of data in both triangulation of sources, methods and time. Further data analysis with interactive data analysis model from Miles and Huberman. The results of this study successfully identified the values of local wisdom for the mitigation and adaptation of landslide disaster that actually existed in the realm of community culture in the District of Lima Puluh Kota. Those values are natural signs, social-cultural bans and powers and information media of local wisdom values in the face of natural disasters such as landslides.